Influencia del bienestar psicológico en el desempeño docente en la Red 13, Ugel 6, Ate, 2020 - Acevedo Cristobal, Anick Soledad (2020)
The present research aimed to establish the Influence of psychological well-being on teacher performance in Network 13, Ugel 6, Ate, 2020, the type of study was explanatory level, the sample was 80 teachers from network 13 UGEL 6 of Ate, for data collection, the survey technique was applied, the instrument was the questionnaire, which was validated by expert judgment and subjected to a Cronbach's alpha reliability test. The results indicate that 42.3% of the teachers surveyed presented a low level of psychological well-being, 34% showed a medium level and 23.7% presented a low level. Likewise, the results obtained in terms of teaching performance showed that 29.9% presented a low level, 45.4% a medium level and 14.7% a high level. It was concluded that there is a significant dependence of psychological well-being on teacher performance (sig. = 0.000; Chi square = 137.516) and the value of Nagelkerke = 0.860 indicates that 86% of the variation of teacher performance is explained by the variable psychological well-being in La Red 13- Ugel- 06 Ate, 2020